The Role of the "Three" in the Text History of the Septuagint: II. Aspects of Interdependence of the Old Greek and the Three in Ecclesiastes - Gentry, Peter J. (Aramaic studies, 2006)
This study elucidates corruption and influence from the versions of the Three Jewish Revisors (Aquila, Symmachus, and Theodotion) on the textual transmission of the Greek Ecclesiastes and its congeners, especially the Old Latin, as well as corruption of the textual transmission of the Three from the LXX. In some cases, the incestuous relationship between the LXX and the Three cannot be sorted out. The Syro-Hexapla, the Syriac translation of the hexaplaric text, is one of the most important and reliable witnesses to the hexaplaric group and to the Three. The analysis clarifies considerably the text history of the LXX Ecclesiastes.